The Protecting Effects and Mechanisms of Baicalin and Octreotide on Heart Injury in Rats with SAP - Zhang Xiping; Tian Hua; Chen Hanqing; Chen Li; Wang Zhiwei; Wang Keyi; Yan Wei; Li Yun; Li Qingyu; He Qing; Wang Fei (Mediators of Inflammation)
Purpose. To observe the protecting effects and mechanisms of Baicalin and Octreotide on heart injury in rats with severe acute pancreatitis (SAP). Methods. The SAP rat models were randomly divided into the model group, Baicalin-treated group, Octreotide treated group, and sham operation group. The contents of some inflammatory indexes in blood were determined. The rat mortality, pathological changes of heart, the changes of NF-κB, P-Selectin, Bax, Bcl-2, and Caspase-3 protein expression levels as well as apoptotic index were observed in all groups, respectively, at 3 hours, 6 hours, and 12 hours after operation. Results. The survival rate of model group was less than treated groups at 12 hours, difference was significant. The contents of some inflammatory indexes of the treated groups were lower than those of the model group to various degrees at different time points. The pathological myocardial changes under light microscope were milder in treated groups than in model group. The changes of NF-κB, P-Selectin, Bax, Bcl-2, and Caspase-3 protein expression levels in all groups were different. There was only a case of myocardial cell apoptosis in an Octreotide-treated group at 6 hours. Conclusion. Baicalin and Octreotide have protecting effects on heart injury of rats with SAP.